Bridging the Gap? Ex-Military Personnel and Military–Civilian Transition Within the Prison Workforce. Issue 1 (January 2023) - Turner, Jennifer; Moran, Dominique
Prior research into military–civilian transition has suggested that the Prison Service may be a popular destination for Armed Forces leavers, but the experience of former military personnel within the prison system as prison staff (rather than as Veterans in Custody) has so far been overlooked. As a result, we know very little about their route into prison work. This article reports on a UK study investigating the experience of prison personnel who have previously served in the military and presents the first set of empirical evidence addressing these critical questions. Whilst our findings mirror prevailing assumptions of a relatively seamless transition to post-military careers (and, in particular, those within Protective Service Occupations), few had intended a career in prison work specifically. Such trajectories may influence personal military–civilian transitions, as well as job performance in prison work and, by extension, the everyday lives of prisoners and other prison staff.